Does surgical treatment of nasal airway obstruction improve sexual functions?. Issue 9 (29th August 2019) - Cayir, S; Hizli, O; Gul, M
Abstract: Objective: To investigate the effects of surgical treatment for nasal obstruction on sexual functions, regardless of the condition causing the nasal obstruction. Methods: Of 238 patients identified with nasal obstruction, 57 complained of erectile dysfunction and were included in the analysis. Patients underwent septoplasty, functional endoscopic sinus surgery, concha bullosa excision or radiofrequency ablation of the inferior turbinates, depending on their obstruction-causing disease. Pre- and post-operative evaluation of perceived nasal obstruction was performed using the Nasal Obstruction Symptom Evaluation questionnaire. Pre- and post-operative assessment of sexual functions was performed using the International Index of Erectile Function. Results: Mean post-operative scores for erectile function, orgasmic function, sexual desire, intercourse satisfaction and overall sexual satisfaction were significantly higher compared to the pre-operative scores ( p = 0.022, p = 0.036, p = 0.033, p = 0.016 and p = 0.029, respectively). Conclusion: Surgical treatment of nasal obstruction by septoplasty, endoscopic sinus surgery, concha bullosa excision or radiofrequency can significantly improve sexual performance.